Enkapsulasi Urea Pada Lumpur PDAM-Alginat sebagai Pupuk Lepas Lambat - Astar, Ismail; Ayu Suci, Ida (Al-Kimia, 2022)
Modification of sludge solid waste regional water company (PDAM) Pontianak with alginate for the application of slow-release urea fertilizer. Characterization of materials was performed with Fourier-Transform Infra-Red (FTIR) spectroscopy and scanning electron microscopy (SEM). Analysis of the FTIR spectrum obtained showed that the characteristics of the absorption band at wavelengths of 3639.89 cm-1 and 3690.9 cm-1 are characteristic of the vibration of NH2 stretching asymmetric and symmetric derived from the presence of urea. Nitrogen release tests on mud PDAM-alginate composites with concentrations of 10%, 20%, 30%, 40% and 50% for 72 consecutive hours of 12,80%, 19,33%, 4,00%, 8,39% and 6,20%. This shows that urea encapsulated mud PDAM-alginate at a concentration of 30% is the composition with the best results in holding urea encapsulated.